The Poverty/Environment Nexus in Cambodia and Lao People's Democratic Republic - Dasgupta, Susmita; Deichmann, Uwe; Meisner, Craig; Wheeler, David (World Bank, Washington, DC, 2014)
Environmental degradation can inflict serious damage on poor people because their livelihoods often depend on natural resource use and their living conditions may offer little protection from air, water, and soil pollution. At the same time, poverty-constrained options may induce the poor to deplete resources and degrade the environment at rates that are incompatible with long-term sustainability. In such cases, degraded resources may precipitate a downward spiral, by further reducing the income and livelihoods of the poor. This "poverty/environment nexus" has become a major issue in the recent literature on sustainable development. In regions where the nexus is significant, jointly addressing problems of poverty and environmental degradation may be more cost-effective than addressing them separately. Empirical evidence on the prevalence and importance of the poverty/environment nexus is sparse because the requisite data are often difficult to obtain in developing countries. The authors use newly available spatial and survey data to investigate the spatial dimension of the nexus in Cambodia, and Lao People's Democratic Republic. The data enable the authors to quantify several environmental problems at the district and provincial level. In a parallel exercise, they map the provincial distribution of poor households. Merging the geographic information on poverty and the environment, the authors search for the nexus using geo-referenced indicator maps and statistical analysis. The results suggest that the nexus is country-specific: geographical, historical, and institutional factors may all play important roles in determining the relative importance of poverty and environment links in different contexts. Joint implementation of poverty and environment strategies may be cost-effective for some environmental problems, but independent implementation may be preferable in many cases as well. Since the search has not revealed a common nexus, the authors conclude on a cautionary note. The evidence suggests that the nexus concept can provide a useful catalyst for country-specific work, but not a general formula for program design.